2021
DOI: 10.1002/er.6375
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐plating‐free fast charging of large‐format lithium‐ion batteries with reference electrodes

Abstract: Fast charging without lithium deposition has been one of the most important goals for commercial lithium-ion batteries. This study developed a fast charging strategy for a commercial large-format NCM/graphite lithium-ion battery with a nominal capacity of 120 Ah. Reliable reference electrodes, whose performances were thoroughly investigated with high fidelity, were implanted into the cells to provide anode potential signals during the charging process. The charging current was strictly modulated to maintain bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 55 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…As other examples of utilizing EP-based charging approaches, papers [86] and [87] get benefits of implanting reference electrodes to achieve a faster charging. It has been reported that [87] implanted reliable reference electrodes within the cells in order to provide anode potential signals throughout the charging process, whose performances were thoroughly investigated. Accordingly, both anode potential and temperature were strictly maintained within the safety regions with the charger current modulated.…”
Section: Electrochemical-parameter-based Charging Methodsmentioning
confidence: 99%
“…As other examples of utilizing EP-based charging approaches, papers [86] and [87] get benefits of implanting reference electrodes to achieve a faster charging. It has been reported that [87] implanted reliable reference electrodes within the cells in order to provide anode potential signals throughout the charging process, whose performances were thoroughly investigated. Accordingly, both anode potential and temperature were strictly maintained within the safety regions with the charger current modulated.…”
Section: Electrochemical-parameter-based Charging Methodsmentioning
confidence: 99%
“…Liu et al [16] introduced a novel fast-charging approach that hinges on real-time monitoring of the negative electrode potential and adjusting the charging current dynamically. The negative electrode potential is measured by a reference electrode inserted between the anode and cathode and shielded by a separator (Figure 2).…”
Section: Sensing Of Internal Electrode Potentialmentioning
confidence: 99%
“…However, it's important to acknowledge that realworld conditions can introduce losses during the charging process. Observations have shown that approximately 40% of these losses occur during battery charging because the battery is not an ideal voltage source [39], [40]. However, charging efficiency can vary based on various factors including the type of battery, the state of charge, temperature, and the quality of the charger.…”
Section: B Battery Charging Current and Charging Duration Specificationsmentioning
confidence: 99%